Utilization of water mimosa (Neptunia oleracea) leaf meal in concentrate feed to improve the growth of Kalimantan swamp buffalo calves - Sumantri, Ika; Hadian, Gloria Rida; Rizal, Muhammad; Widi, TriSatya Mastuti; Prastowo, Sigit (TROPICAL WETLAND JOURNAL, 2023)
Swamp buffalo on Kalimantan island is reared under an extensive production system. Minimum farmer input and decreasing swamp grass availability during the wet season lead to lower buffalo morphometrics, lower reproductive performances, and a higher calf mortality rate. This participatory study was conducted to evaluate the calf's performance after receiving a concentrate feed formulated using water mimosa (Neptunia oleracea) leaf meal as a protein source. Results of the study showed that water mimosa leaf meal has high crude protein content (>30%). After 4 months of observation, feeding concentrate feed formulated with water mimosa leaf meal as a protein source improved the growth of swamp buffalo calves. The calves in concentrate feed group showed body weight gain of 14.84 kg/month, growths of chest girth 13.6 cm, and height at wither 5.6 cm those improved compared to those in the group that did not offer concentrate feed that had the growths in chest girth 9.2 cm and height at wither 5.2 cm. This study provides valuable insights into the potential of using water mimosa leaf meals as a protein source for concentrate feed, which can enhance the growth of buffalo calves while resolving the issue of water mimosa invasion in the swamp area.